Policies for development of unified and compatible software technology system for setting up cadastral database for modernization of land management sector in Vietnam - Khoa, Doan Van (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2017)
Land management is a “hot” topic in Vietnam during recent years. The successful setting-up of a cadastral database for modernization of S&T based land management sector has a very important value. Actually, numerous softwares for land management are introduces to use in Vietnam but there is not high level compatibility between them. Therefore, the products cannot provide effective management to meet social needs. On basis of surveys and analysis of in-use softwares for cadastral database, this paper proposes policies to develop a unified and compatible software technology system to enhance effective land management works. Code: 13062901